2002
DOI: 10.1021/es010326n
|View full text |Cite
|
Sign up to set email alerts
|

Humic Colloid-Borne Natural Polyvalent Metal Ions:  Dissociation Experiment

Abstract: The natural association nature of the humic colloid-borne trace elements is investigated. Rare earth elements (REE) Th and U are chosen as naturally occurring representatives and chemical homologues for actinides of different oxidation states present in nuclear waste. Tri- and tetravalent elements in two investigated Gorleben groundwaters (Gohy-532 and -2227) almost exclusively occur as humic or fulvic colloid-borne species. Their desorption behavior from colloids is examined in the unperturbed groundwater (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 34 publications
(47 reference statements)
6
99
0
Order By: Relevance
“…Binding of higher-valent metals to humic substances has been reported to be accompanied by time-dependent transformations that entail a decreasing availability to competing ligands in dissociation experiments (Van den Bergh et al, 2001;Geckeis et al, 2002). Such findings are of some importance in view of current modelling strategies, which are based on thermodynamic equilibrium constants.…”
Section: Introductionmentioning
confidence: 94%
“…Binding of higher-valent metals to humic substances has been reported to be accompanied by time-dependent transformations that entail a decreasing availability to competing ligands in dissociation experiments (Van den Bergh et al, 2001;Geckeis et al, 2002). Such findings are of some importance in view of current modelling strategies, which are based on thermodynamic equilibrium constants.…”
Section: Introductionmentioning
confidence: 94%
“…ions and the Table 1) are shown in Fig. 5b [54,55]. The results demonstrate that Eu(III) presents in the forms of Eu 3?…”
Section: Effect Of Ph and Ionic Strengthmentioning
confidence: 73%
“…They have reported sorption coefficients K d which were 1-2 orders of magnitude higher with tracers than their counterpart in contaminated groundwater. Geckeis, Rabung, Ngo, Kim, and Beck (2002) have reported that naturally present Eu in groundwaters (associated with colloidal material) behaved differently from the Eu added from artificial solutions. Desorption of naturally occurring Eu was slow (>100 d and still not finalized), whereas desorption of artificially added Eu was fast.…”
Section: Introductionmentioning
confidence: 99%